Equal treatment of shareholders - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Equal treatment of shareholders is regulated in Art.269 of Company Act (2011) of Republic of Serbia. Equal treatment of shareholders means that all shareholders are to be treated equally under same circumstances. Obligation to treat all shareholders equally rests on all company bodies, predominantly general meeting. The standard whether an action violates the principle of equal treatment of all shareholders regarding the main rights of shareholders (such as voting right etc.) is the nominal value of shares, or the equal treatment per person regarding ancillary rights (such as right to speak in shareholders’ meeting etc.). Any action deviating from this standard is unlawful if the unequal treatment is not justified on the facts. If the principle of equal treatment is violated by general meeting resolution, such resolution may be annulled by the court.